2004
DOI: 10.1002/anie.200460637
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Monodeprotonation of Bis(benzene)chromium by Using Mixed Alkali Metal–Magnesium Amide Bases and Structural Characterization of the Heterotrimetallic Products

Abstract: The spotlight is on the classical organometallic molecule bis(benzene)chromium, which this year celebrates its 50th anniversary. Easy to dimetalate, its monometalation on a preparative scale has thus far proved elusive. The synergic action of Na/Mg or K/Mg bases allows its selective deprotonation. For more information, see the Communication by R. E. Mulvey and co-workers on the following pages. 68

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Both compounds, 10 and 11, crystallise from toluene solutions. The affinity of heavy alkali metals to engage π-interactions with arenes is well known; 42,[80][81][82][83][84][85][86] however, in the presence of the corresponding multidentate ligands TMDAE and TMEEA in 10 and 11, respectively, there is no interaction with the arene in the solid-state structures.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…Both compounds, 10 and 11, crystallise from toluene solutions. The affinity of heavy alkali metals to engage π-interactions with arenes is well known; 42,[80][81][82][83][84][85][86] however, in the presence of the corresponding multidentate ligands TMDAE and TMEEA in 10 and 11, respectively, there is no interaction with the arene in the solid-state structures.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…From these solid-state data, the authors were able to rationalize a key step in the reaction pathway of the aldol reaction. Over the past few years we have shown that heterobimetallic alkali-metal/divalent-metal TMP-containing complexes (such as the zincate [75] can induce a special synergic chemistry culminating in the regioselective alkali-metalmediated magnesiation/zincation of arenes [76][77][78][79][80][81][82][83] and metallocenes [84][85][86][87][88][89] and opening up the concept of inverse crown chemistry. [90,91] To build up a full understanding of the chemistry of the mixed metal systems, for example, the aforementioned Na-Zn system, [75] we have decided to turn our attention to the TMEDA complexes of the component alkali-metal amide reagents.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mixing equimolar quantities of butylpotassium and dibutylmagnesium with three molar equivalents of TMPH in arenes such as benzene results in single metalation of the aromatic ring. 26 In contrast, single lithiation using reagents such as BuLi/TMEDA is problematic due to the first lithiation activating the second ring to metalation, resulting in doubly metalated products. In contrast, replacing butylpotassium with butylsodium results in double deprotonation of benzene at the 1,4-positions, and toluene at the 2,5-positions.…”
Section: Mixed Metal Basesmentioning
confidence: 99%